Evaluation of tandem repeats for MLVA typing of Streptococcus uberis isolated from bovine mastitis - Lamoureux Jérémy; Fromageau Angélina; Gilbert Florence B; Poutrel Bernard (BMC Veterinary Research, 2006)
Abstract Background Streptococcus uberis is a common cause of bovine mastitis and recommended control measures, based on improved milking practice, teat dipping and antibiotic treatment at drying-off, are poorly efficient against this environmental pathogen. A simple and efficient typing method would be helpful in identifying S.uberis sources, virulent strains and cow to cow transmission. The potential of MLVA (Multiple Loci VNTR Analysis; VNTR, Variable Number of Tandem Repeats) for S. uberis mastitis isolates genotyping was investigated. Results The genomic sequence of Streptococcus uberis (strain 0104J) was analyzed for potential variable number tandem repeats (VNTRs). Twenty-five tandem repeats were identified and amplified by PCR with DNA samples from 24 S. uberis strains. A set of seven TRs were found to be polymorphic and used for MLVA typing of 88 S. uberis isolates. A total of 82 MLVA types were obtained with 22 types among 26 strains isolated from the milk of mastitic cows belonging to our experimental herd, and 61 types for 62 epidemiologically unrelated strains, i.e. collected in different herds and areas. Conclusion The MLVA method can be applied to S. uberis genotyping and constitutes an interesting complement to existing typing methods. This method, which is easy to perform, low cost and can be used in routine, could facilitate investigations of the epidemiology of S. uberis mastitis in dairy cows.